Hydrologic pulsing promotes spatial connectivity and food web subsidies in a subtropical coastal ecosystem - Garcia, A. M.; Winemiller, K. O.; Hoeinghaus, D. J.; Claudino, M. C.; Bastos, R.; Correa, F.; Huckembeck, S.; Vieira, J.; Loebmann, D.; Abreu, P.; Ducatti, C. [UNESP] (Inter-research, 2017)
Resource pulsing is a widespread phenomenon, but its effects on ecosystem dynamics are often difficult to predict. Hydrological pulsing, in particular, is known to influence the structure and dynamics of fluvial and coastal ecosystems, but little information is available about its effects on trophic connectivity between wetlands and estuaries. We investigated the hypothesis that hydrologic pulsing drives 1-way trophic subsidies (e.g. suspended organic matter and freshwater fish) from wetland to estuary. Our study system is a coastal lagoon with an ephemeral mouth that, when closed, stores freshwater as a sustained flood pulse that is subsequently released when a connection with the sea is reestablished. We monitored isotopic composition of consumers and food sources over the course of an entire flood pulse to infer trophic linkages and spatial subsidies. Before the flood peak (April and May), freshwater and estuarine zones were largely dependent on local primary production sources (seston and C-3 plants vs. C-4 plants and microphytobenthos, respectively), essentially functioning as disconnected compartments. A sustained pulse of freshwater inflow (June to August) induced greater habitat connectivity and a net flow of biomass and energy from the freshwater zone into the estuarine zone. The opening of the lagoon outlet channel abruptly terminated the flood pulse and reduced freshwater subsidies to estuarine consumers, and both zones returned to dependence on autochthonous production. Our findings contribute to current concerns that artificial opening of sandbars in coastal lagoons alters natural ecological dynamics with significant effects on biodiversity and ecosystem processes.
Keywords: Basal resource; Bayesian mixing model; Biomass assimilation; Estuary; Hydrologic connectivity; Production source; Salinity; Trophic ecology